The sustaining of Sarawak cultural fashion among the youths of Sarawak / Dayana Amalina Mohamad Zen and Muhammad Fauzan Abu Bakar - Mohamad Zen, Dayana Amalina; Abu Bakar, Muhammad Fauzan (UiTM Cawangan Johor, 2023)
"Culture" fashion, especially from different ethnicities, evolves from one side of ethnicity beliefs and culture it self. "Culture" fashion is not just for the trend, but it represents ethnicity through the concepts, detailing, preserving, and accepting the youths in Sarawak. Preserving the "culture" also ensures that the new generation will further follow the "culture" presented today. As the "culture" fashion keeps changing, it is most important to figure out how to maintain or sustain it so the Sarawak culture will be the most priceless asset that should never be faded away. The study has executed survey questionnaires, and 160 respondents have participated. The result shows specific patterns towards the acceptance of Cultural Fashion in Sarawak among the youths. It shows that youths have different perspectives on accepting cultural fashion as part of their daily lives. Thus, it is important to consider multiple strategies to execute cultural fashion to sustain it as part of Sarawak Fashion Industries. Keywords: Cultural Fashion, Sustainable Culture, Sarawak's Youth, Fashion Retailing.